Acceptability and Feasibility of a Pharmacist-Led Human Immunodeficiency Virus Pre-Exposure Prophylaxis Program in the Midwestern United States. (14th August 2019) - Havens, Joshua P; Scarsi, Kimberly K; Sayles, Harlan; Klepser, Donald G; Swindells, Susan; Bares, Sara H
Abstract: Background: Human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) substantially reduces the risk of HIV acquisition, yet significant barriers exist to its prescription and use. Incorporating pharmacists in the PrEP care process may help increase access to PrEP services. Methods: Our pharmacist-led PrEP program (P-PrEP) included pharmacists from a university-based HIV clinic, a community pharmacy, and 2 community-based clinics. Through a collaborative practice agreement, pharmacists conducted PrEP visits with potential candidates for PrEP, according to the recommended Centers for Disease Control and Prevention guidelines, and authorized emtricitabine-tenofovir disoproxil fumarate prescriptions. Demographics and retention in care over 12 months were summarized, and participant satisfaction and pharmacist acceptability with the P-PrEP program were assessed by Likert-scale questionnaires. Results: Sixty patients enrolled in the P-PrEP program between January and June 2017 completing 139 visits. The mean age was 34 years (range, 20–61 years), and 88% identified as men who have sex with men, 91.7% were men, 83.3% were white, 80% were commercially insured, and 89.8% had completed some college education or higher. Participant retention at 3, 6, 9, and 12 months was 73%, 58%, 43%, and 28%, respectively. To date, no participant has seroconverted. One hundred percent of the participants who completed the patient satisfaction questionnaire would recommend the P-PrEP program. Pharmacists reported feeling comfortable performing point-of-care testing and rarely reported feeling uncomfortable during PrEP visits (3 occasions, 2.2%) or experiencing workflow disruption (1 occasion, 0.7%). Conclusions: Implementation of a pharmacist-led PrEP program is feasible and associated with high rates of patient satisfaction and pharmacist acceptability.